Acoustic Emission and Damage Characteristics of Granite Subjected to High Temperature - X. L. Xu; Z.-Z. Zhang (Advances in Materials Science and Engineering)
Acoustic emission (AE) signals can be detected from rocks under the effect of temperature and loading, which can be used to reflect rock damage evolution process and predict rock fracture. In this paper, uniaxial compression tests of granite at high temperatures from 25°C to 1000°C were carried out, and AE signals were monitored simultaneously. The results indicated that AE ring count rate shows the law of “interval burst” and “relatively calm,” which can be explained from the energy point of view. From 25°C to 1000°C, the rock failure mode changes from single splitting failure to multisplitting failure, and then to incomplete shear failure, ideal shear failure, and double shear failure, until complete integral failure. Thermal damage (DT) defined by the elastic modulus shows logistic increase with the rise of temperature. Mechanical damage (DM) derived by the AE ring count rate can be divided into initial stage, stable stage, accelerated stage, and destructive stage. Total damage (D) increases with the rise of strain, which is corresponding to the stress-strain curve at various temperatures. Using AE data, we can further analyze the mechanism of deformation and fracture of rock, which helps to gather useful data for predicting rock stability at high temperatures.